An electrolyte for micro-arc oxidation and its application, as well as orthopedic implant material and its preparation method
By using an electrolyte containing phosphate, strong alkali and water for microarc oxidation, a porous coating with high porosity and three-dimensional structure is formed, which solves the problem of poor surface modification effect of zinc alloys in the prior art, and significantly improves the corrosion resistance and biocompatibility of zinc-based materials.
Patent Information
- Application Number
- CN202211338459.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-28
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-10-28
AI Technical Summary
The prior art uses microarc oxidation to modify the zinc alloy surface, the coating structure is single, the holes are independent, and the effect is limited in improving the corrosion resistance and biocompatibility of the zinc alloy.
Microarc oxidation is performed using an electrolyte including phosphate, strong alkali and water to form a porous coating with a three-dimensional structure and high porosity, which improves the biocompatibility and corrosion resistance of zinc alloys.
A three-dimensional structure coating with randomly distributed micro-nanopores and in-situ grown particles was achieved on the surface of zinc alloy, which significantly improved the corrosion resistance of zinc-based materials and the adhesion and proliferation ability of osteoblasts.
Smart Images

Figure CN115896897B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of medical materials, and in particular to an electrolyte for micro-arc oxidation and application thereof, and an orthopedic implant material and a preparation method thereof. Background Art
[0002] Zinc-based biodegradable metals have good biocompatibility, significant biological efficacy, and a standard potential between magnesium-based and iron-based metals. In theory, they have a more suitable degradation and absorption rate. They have shown great application potential in the field of bone fixation implants and have gradually attracted the attention of scholars. However, the rapid degradation of zinc alloys will lead to the accumulation of Zn in the human body. 2+ Concentrations exceeding the safety threshold lead to cytotoxicity. This shows that modification technology is the main way to solve the above problems. On the one hand, surface modification technology can build microstructures on the surface of zinc alloys to improve their surface cell compatibility; on the other hand, the preparation of coatings can solve the problem of zinc alloys being degraded too quickly when used as medical materials.
[0003] Micro-arc oxidation (MAO) is a new surface modification technology with simple process, high efficiency and green environmental protection. It is through the combination of electrolyte and corresponding parameters, relying on the instantaneous high temperature and high pressure generated by arc discharge on the alloy surface, to in-situ grow a ceramic porous coating mainly composed of matrix metal oxide.
[0004] At present, there are relatively few studies on surface modification of zinc alloys using micro-arc oxidation. The prepared coatings are mostly crater-shaped or discrete porous structures. These surface structural pores are independent of each other and the structural scale is relatively single. At the same time, the improvement effect in improving the corrosion resistance and biocompatibility of zinc alloys is limited. Summary of the invention
[0005] In view of this, the object of the present invention is to provide an electrolyte for micro-arc oxidation, which can form a porous coating with a three-dimensional structure and high porosity on the surface of a zinc alloy and increase the adhesion and proliferation of osteoblasts when used for preparing a coating by micro-arc oxidation;
[0006] Another object of the present invention is to provide the use of the above electrolyte in the preparation of orthopedic implant materials;
[0007] Another object of the present invention is to provide an orthopedic implant material obtained based on the above electrolyte.
[0008] In order to solve the above technical problems or at least partially solve the above technical problems, the present invention provides a method for solving the above technical problems or at least partially solving the above technical problems. As a first aspect of the present invention, an electrolyte for micro-arc oxidation is provided, comprising phosphate, strong alkali and water.
[0009] Optionally, the concentration of the phosphate is 20 to 30 g / L; further optionally, the phosphate is one or more of sodium phosphate, disodium hydrogen phosphate, and sodium dihydrogen phosphate.
[0010] Optionally, the concentration of the strong base is no more than 5 g / L; further optionally, the strong base is sodium hydroxide or potassium hydroxide.
[0011] As a second aspect of the present invention, provided is the use of the electrolyte in preparing orthopedic implant materials.
[0012] As a third aspect of the present invention, an orthopedic implant material is provided, wherein a coating formed by micro-arc oxidation with the electrolyte of the present invention is provided on the surface of the zinc alloy.
[0013] Optionally, Zn in the zinc alloy is ≥ 99.99%.
[0014] As a fourth aspect of the present invention, a method for preparing the orthopedic implant material is provided, comprising:
[0015] Step 1: Pre-treatment of the zinc alloy material by grinding, degreasing and cleaning;
[0016] Step 2: The pretreated zinc alloy material is used as the positive electrode and micro-arc oxidation is performed in the electrolyte of the present invention.
[0017] Compared with the prior art, the present invention has at least the following advantages:
[0018] (1) The coating prepared by the micro-arc oxidation electrolyte on the surface of the zinc alloy has a zinc oxide coating with high porosity and three-dimensional structure, and the coating has randomly distributed micro-nano pores and in-situ grown particles;
[0019] (2) The coating prepared on the surface of the zinc alloy by the micro-arc oxidation electrolyte of the present invention not only significantly improves the corrosion rate of the zinc-based material, but also can improve the adhesion and proliferation of osteoblasts, thereby promoting the application of medical zinc-based materials in the preparation of orthopedic implants;
[0020] (3) The preparation method of the present invention is green and environmentally friendly, with simple process and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Shown are 500 and 2000 times SEM images of the porous coating prepared in Example 1 of the present invention;
[0022] Figure 2 The polarization curve of the porous coating prepared in Example 1 of the present invention is shown; wherein pure zinc means zinc alloy;
[0023] Figure 3Shown are 500 and 2000 times SEM images of the porous coating prepared in Example 2 of the present invention;
[0024] Figure 4 The polarization curve of the porous coating prepared in Example 2 of the present invention is shown; wherein pure zinc means zinc alloy;
[0025] Figure 5 Shown are 500 and 2000 times SEM images of the porous coating prepared in Example 3 of the present invention;
[0026] Figure 6 The polarization curve of the porous coating prepared in Example 3 of the present invention is shown; wherein pure zinc means zinc alloy;
[0027] Figure 7 The figure shows the comparison of cell proliferation rates of the coatings prepared in Comparative Example 1 and Example 1 of the present invention; wherein pure zinc refers to zinc alloy. DETAILED DESCRIPTION
[0028] The present invention discloses an electrolyte for micro-arc oxidation and its application, and an orthopedic implant material and its preparation method. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in the present invention. The products, preparation methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the products, preparation methods and applications described herein without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention.
[0029] In the first aspect of the present invention, the electrolyte for micro-arc oxidation comprises phosphate, strong alkali and water.
[0030] In some embodiments of the present invention, the concentration of the phosphate is 20-30 g / L; in other embodiments of the present invention, the concentration of the phosphate can be selected from 20 g / L, 25 g / L or 30 g / L. In other embodiments of the present invention, the phosphate is one or more of sodium phosphate, disodium hydrogen phosphate and sodium dihydrogen phosphate.
[0031] In certain embodiments of the present invention, the concentration of the strong base is no more than 5 g / L; in other embodiments of the present invention, the concentration of the strong base is 1 g / L, 2 g / L, 3 g / L, 4 g / L or 5 g / L; in other embodiments of the present invention, the strong base is sodium hydroxide or potassium hydroxide; in other embodiments of the present invention, comparative experiments have verified that the addition of strong base helps promote the adhesion and proliferation of osteoblasts.
[0032] The electrolyte can be arbitrarily selected from the following compositions:
[0033] (1) Sodium phosphate, sodium hydroxide and water;
[0034] (2) sodium dihydrogen phosphate, sodium hydroxide and water;
[0035] (3) Disodium hydrogen phosphate, sodium hydroxide and water.
[0036] In the second aspect of the present invention, the coating prepared by micro-arc oxidation using the electrolyte of the present invention is superior in corrosion resistance and in promoting the adhesion and proliferation of osteoblasts compared to the coating prepared by pure zinc alloy and the electrolyte without using a strong alkali, and the coating has a three-dimensional structure composed of randomly distributed micro-nanopores and in situ grown particles and a high porosity, thereby proposing the application of the electrolyte in the preparation of orthopedic implant materials.
[0037] In a third aspect of the present invention, an orthopedic implant material is provided, wherein a coating formed by micro-arc oxidation with the electrolyte of the present invention is provided on the surface of the zinc alloy.
[0038] In certain embodiments of the present invention, Zn in the zinc alloy is ≥99.99%; in other embodiments of the present invention, the pure zinc material is No. 0 pure zinc, and more specifically, the element composition (mass fraction) of No. 0 pure zinc is: Al 0.001%, Mg 0.0003%, Fe 0.001%, Cu 0.003%, Pb 0.0005%, Cd 0.0001%, Sn 0.0002%, and Zn ≥99.99%.
[0039] In a fourth aspect of the present invention, a method for preparing the orthopedic implant material is provided, comprising:
[0040] Step 1: Pre-treatment of the zinc alloy material by grinding, degreasing and cleaning;
[0041] Step 2: The pretreated zinc alloy material is used as the positive electrode and micro-arc oxidation is performed in the electrolyte of the present invention.
[0042] In certain embodiments of the present invention, the zinc alloy material is polished step by step, ultrasonically cleaned with acetone, anhydrous ethanol and water, and then degreased and cleaned with an alkaline degreasing liquid. The step-by-step polishing is performed with silicon carbide sandpaper with increasing numbers, and the polishing degree is until the surface is bright without obvious scratches and the texture is consistent. The alkaline degreasing liquid is sodium hydroxide, which can be a 10% sodium hydroxide solution.
[0043] In certain embodiments of the present invention, the micro-arc oxidation is carried out in an AC constant voltage mode, and the processing parameters are: forward voltage +150V to +250V, negative voltage -20V to -40V, pulse frequency is fixed at 0.1 to 0.3Hz, and duty cycle is set to 70% to 90%.
[0044] In certain embodiments of the present invention, zinc alloy material is used as the positive electrode and other suitable metals such as stainless steel are used as the negative electrode, and the distance between the positive and negative electrodes is controlled at 10 cm; the temperature of the electrolyte is controlled by an internal and external circulation refrigeration device to maintain at 25-35°C.
[0045] In some other embodiments of the present invention, a method for preparing the orthopedic implant material is specifically provided, comprising:
[0046] 1. Pretreatment of zinc substrate
[0047] Cutting, grinding, and solvent ultrasonic cleaning of zinc alloy materials;
[0048] 2. Ultrasonic degreasing
[0049] Immerse the bright and clean pure zinc material in alkaline degreasing liquid, then perform ultrasonic cleaning and dry;
[0050] 3. Prepare micro-arc oxidation electrolyte
[0051] Dissolving phosphate and sodium hydroxide into deionized water and stirring evenly to obtain a micro-arc oxidation electrolyte;
[0052] 4. Micro-arc oxidation
[0053] The surface pretreated zinc alloy is placed in a micro-arc oxidation electrolyte, wherein the zinc alloy is connected to the positive electrode of the power supply as the positive electrode, and the stainless steel electrolytic cell is connected to the negative electrode of the power supply as the negative electrode; the refrigeration device is turned on to control the temperature; the micro-arc oxidation AC pulse power supply is used to start power supply, and the positive and negative voltages in the constant voltage mode are respectively +150V to +250V, the negative voltage is -20V to -40V, the pulse frequency is fixed at 0.1 to 0.3Hz, and the duty cycle is set to 70% to 90%, and micro-arc oxidation is performed to obtain a zinc alloy material (orthopedic implant material) with a micro-arc oxidation coating on the surface;
[0054] 5. Board post-processing
[0055] All samples were rinsed with deionized water and dried at ambient temperature.
[0056] Unless otherwise specified, the experimental environment and parameter conditions of each group in the test remained consistent except for the differences explicitly stated.
[0057] The following further describes an electrolyte for micro-arc oxidation and its application, and an orthopedic implant material and its preparation method provided by the present invention.
[0058] Example 1: Preparation of orthopedic implant material with porous coating
[0059] 1. Pretreatment of pure zinc substrate
[0060] Cutting, grinding, and solvent ultrasonic cleaning of pure zinc materials;
[0061] 2. Ultrasonic degreasing
[0062] Immerse the bright and clean pure zinc material in alkaline degreasing liquid, then perform ultrasonic cleaning and dry;
[0063] 3. Prepare micro-arc oxidation electrolyte
[0064] Dissolve 25 g / L sodium phosphate and 1 g / L sodium hydroxide in deionized water and stir evenly to obtain a micro-arc oxidation electrolyte;
[0065] 4. Micro-arc oxidation
[0066] The pure zinc after surface pretreatment is placed in a micro-arc oxidation electrolyte, wherein the pure zinc is connected to the positive electrode of the power supply as the positive electrode, and the stainless steel electrolytic cell is connected to the negative electrode of the power supply as the negative electrode; the refrigeration device is turned on to control the temperature; the micro-arc oxidation AC pulse power supply is used to start power supply, and the positive and negative voltages in the constant voltage mode are +200V and -20V respectively, the pulse frequency is fixed at 0.2Hz, and the duty cycle is set to 80%, and micro-arc oxidation is performed to obtain a pure zinc material with a micro-arc oxidation porous coating on the surface;
[0067] 5. Board post-processing
[0068] All samples were rinsed with deionized water and dried at ambient temperature.
[0069] Figure 1 Shown are 500 and 2000 times SEM images of the porous coating prepared in Example 1 of the present invention, indicating that a coating with a three-dimensional structure consisting of randomly distributed micro-nano pores and in-situ grown particles and high porosity is successfully prepared on the zinc alloy surface.
[0070] Electrochemical tests were performed in this embodiment to prepare the polarization curve of the porous coating. Figure 2 As shown, the polarization voltage is -0.077V, and the corrosion resistance is significantly improved.
[0071] Example 2: Preparation of orthopedic implant material with porous coating
[0072] 1. Pretreatment of pure zinc substrate
[0073] Cutting, grinding, and solvent ultrasonic cleaning of pure zinc materials;
[0074] 2. Ultrasonic degreasing
[0075] Immerse the bright and clean pure zinc material in alkaline degreasing liquid, then perform ultrasonic cleaning and dry;
[0076] 3. Prepare micro-arc oxidation electrolyte
[0077] Dissolve 25 g / L sodium dihydrogen phosphate and 2 g / L sodium hydroxide in deionized water and stir evenly to obtain a micro-arc oxidation electrolyte;
[0078] 4. Micro-arc oxidation
[0079] The pure zinc after surface pretreatment is placed in a micro-arc oxidation electrolyte, wherein the pure zinc is connected to the positive electrode of the power supply as the positive electrode, and the stainless steel electrolytic cell is connected to the negative electrode of the power supply as the negative electrode; the refrigeration device is turned on to control the temperature; the micro-arc oxidation AC pulse power supply is used to start power supply, and the positive and negative voltages in the constant voltage mode are +200V and -20V respectively, the pulse frequency is fixed at 0.2Hz, and the duty cycle is set to 80%, and micro-arc oxidation is performed to obtain a pure zinc material with a micro-arc oxidation porous coating on the surface;
[0080] 5. Board post-processing
[0081] All samples were rinsed with deionized water and dried at ambient temperature.
[0082] Figure 3 Shown are 500 and 2000 times SEM images of the porous coating prepared in Example 2 of the present invention, indicating that a coating with a three-dimensional structure consisting of randomly distributed micro-nano pores and in-situ grown particles and high porosity is successfully prepared on the zinc alloy surface.
[0083] Electrochemical tests were performed in this embodiment to prepare the polarization curve of the porous coating. Figure 4 As shown, the polarization voltage is -0.085V, and the corrosion resistance is significantly improved.
[0084] Example 3: Preparation of orthopedic implant material with porous coating
[0085] 1. Pretreatment of pure zinc substrate
[0086] Cutting, grinding, and solvent ultrasonic cleaning of pure zinc materials;
[0087] 2. Ultrasonic degreasing
[0088] Immerse the bright and clean pure zinc material in alkaline degreasing liquid, then perform ultrasonic cleaning and dry;
[0089] 3. Prepare micro-arc oxidation electrolyte
[0090] Dissolve 25 g / L disodium hydrogen phosphate and 2 g / L sodium hydroxide in deionized water and stir evenly to obtain a micro-arc oxidation electrolyte;
[0091] 4. Micro-arc oxidation
[0092] The pure zinc after surface pretreatment is placed in a micro-arc oxidation electrolyte, wherein the pure zinc is connected to the positive electrode of the power supply as the positive electrode, and the stainless steel electrolytic cell is connected to the negative electrode of the power supply as the negative electrode; the refrigeration device is turned on to control the temperature; the micro-arc oxidation AC pulse power supply is used to start power supply, and the positive and negative voltages in the constant voltage mode are +200V and -20V respectively, the pulse frequency is fixed at 0.2Hz, and the duty cycle is set to 80%, and micro-arc oxidation is performed to obtain a pure zinc material with a micro-arc oxidation porous coating on the surface;
[0093] 5. Board post-processing
[0094] All samples were rinsed with deionized water and dried at ambient temperature.
[0095] Figure 5 Shown are 500 and 2000 times SEM images of the porous coating prepared in Example 2 of the present invention, indicating that a coating with a three-dimensional structure consisting of randomly distributed micro-nano pores and in-situ grown particles and high porosity is successfully prepared on the zinc alloy surface.
[0096] Electrochemical tests were performed in this embodiment to prepare the polarization curve of the porous coating. Figure 6 As shown, the polarization voltage is -0.069V, and the corrosion resistance is significantly improved.
[0097] Comparative Example 1: Preparation of coating by electrolyte without adding sodium hydroxide
[0098] Referring to the preparation process of Example 1, sodium hydroxide is not added in step 3;
[0099] The zinc alloy, the implant materials of Example 1 and Comparative Example 1 were tested for biocompatibility, specifically:
[0100] Mouse osteoblast-like cells (MC3T3-E1) were used to evaluate cytocompatibility according to ISO 10993-5:2009. Samples should be sterilized before use. Samples were cultured in α-MEM cell culture medium for 24 hours under standard cell culture conditions, and the material extract was collected at an extraction ratio of 1.25 ml per 1 cm2. The collected extracts were expressed as 100% of the extract. Cells were seeded in 96-well cell culture plates at a density of 5×10 per 100 μL of culture medium. 3cells. The cells were then cultured for 1 day. At the end of the time point, the material extract was replaced with 10% cell counting kit-8 (CCK8, Dojindo, Japan) cell culture medium and cultured at 37°C for 1 hour, and the spectrophotometry of each group was measured at a wavelength of 450 nm by a microplate reader (Bio-RAD680).
[0101] The results are as follows Figure 7 As shown, after one day of cell culture, the proliferation rate in the leaching culture solution of Comparative Example 1 is not only lower than the proliferation rate in the leaching culture solution of Example 1, but also significantly lower than the proliferation rate in the leaching culture solution of zinc alloy (pure zinc). These two comparative examples illustrate that strong alkali has a huge impact on the biocompatibility of the coating, and not adding strong alkali will reduce cell compatibility.
[0102] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An orthopedic implant material, characterized in that: A coating formed by micro-arc oxidation of an electrolyte is provided on the surface of a pure zinc material with Zn≥99.99%; the electrolyte is composed of 20-30 g / L of phosphate, a strong base not greater than 5 g / L, and water; the phosphate is one or more of sodium phosphate, disodium hydrogen phosphate, and sodium dihydrogen phosphate, and the strong base is sodium hydroxide or potassium hydroxide; The micro-arc oxidation is carried out in a constant voltage mode of an AC pulse power supply, and the processing parameters are: a forward voltage of +150V to +250V, a negative voltage of -20V to -40V, a pulse frequency fixed at 0.1 to 0.3 Hz, and a duty cycle set to 70% to 90%.
2. A method for preparing an orthopedic implant material as claimed in claim 1, characterized in that: include: Step 1: Pre-treatment of pure zinc material by grinding, degreasing and cleaning; Step 2: The pretreated pure zinc material is used as the positive electrode, and micro-arc oxidation is performed in the electrolyte described in claim 1; the micro-arc oxidation is performed in a constant voltage mode of an AC pulse power supply, and the processing parameters are: forward voltage +150V~+250V, negative voltage -20V~-40V, pulse frequency is fixed at 0.1~0.3 Hz, and the duty cycle is set to 70%~90%.
Citation Information
Patent Citations
Magnesium base degradable implant material and preparation method thereof
CN101559239A